Current perspectives on rational design of anode electrocatalysts exhibiting CO-tolerance for fuel cells - Choi, Daeil; Park, Subin; Kang, Yun Sik; Yoo, Sung Jong (Elsevier, 2024)
Anode catalysis reduces the cost and remarkably improves the fuel cell performance; however, it is often neglected owing to its fast kinetics. Currently, the majority of hydrogen is obtained by reforming and purifying the hydrocarbons containing impurities such as CO, CO2, and H2S. CO adsorbs more strongly than hydrogen onto the anode catalysts, inhibiting hydrogen oxidation and resulting in performance degradation. Although activity enhancement is essential, impurity tolerance should be preferred over activity for fuel-cell anode catalysts. Various studies have reported improved CO tolerance via lowering the intrinsic CO adsorption energy of the catalyst by tuning the electronic structure or modulating the OH adsorption energy by placing oxophilic materials near the catalysts. Herein, we categorize recent noteworthy studies according to their strategies and present innovative design principles for CO- resistant anode catalysts.